ISLAMIC BRANDING AND MARKETING: AN INSIGHT OF CONSUMER PERCEPTION IN MAKASSAR, INDONESIA (International Conference on Social and Islamic Studies, 2021)
The purpose of this study is to analyze and investigate whether there is a gap between the perceptions of consumers in Makassar, Indonesian Muslim consumers about Islamic branding and marketing and to create a deeper understanding of the perceptions of Indonesian consumers. The research method used is a quantitative method. To answer the question, the researcher used a Likert scale. Initially the scales consisted of 5 alternatives. Starting with strongly disagree (1) then ending with strongly agree (5). Likert scale estimates imply important statistical calculations. Based on the results of the study, it can be concluded that Islamic branding positively affects consumer perception. The majority population of Makassar city is Muslims with strong faith and culture, reflected obviously in their perception of consuming towards halal goods and services that is provided based on Islamic teachings. Islamic brand has to emphasis that is it a brand that holds Halal sources. Then it will bears obvious perception of Islamic brands. Therefore Islamic brands clearly adherents whatever requirement by Sharia’ to be as real Halal brand.